Integration of Educational Games in Indonesian Language Learning at the Senior High School Level: Opportunities and Challenges - Abdul Mukhlis; Antika Bela L.H.; Pertiwi Dian Apriyani (2025)
The integration of technology in Indonesian language learning at the Senior High School level (SMA/MA/SMK) is becoming increasingly important in the digital era. One potential innovation is the use of educational games as a learning medium that can enhance students' motivation, creativity, and understanding in an interactive manner. However, the implementation of educational games also presents various challenges, such as device readiness, teacher skills, and the alignment of content with the curriculum. This study aims to explore the opportunities and challenges of integrating educational games in Indonesian language learning at the senior secondary level, to provide a strategic overview for educators and policymakers. The method used in this research is a literature review, conducted by examining various literatures and previous research related to the utilization of educational games and innovative learning in the digital era. After the data is collected through the literature review, a descriptive qualitative analysis is carried out as the next step to interpret the data. The results indicate that the integration of educational games has great potential to enrich the teaching and learning process, increase student engagement, and support the success of Indonesian language learning. However, this study also reveals technical barriers, including the critical role of teachers in guiding the use of games, the need for adaptive content development, and its compatibility with curriculum standards. This study is expected to contribute both theoretically and practically to the development of innovative learning models based on digital technology, especially educational games. Furthermore, the findings can serve as a reference for teachers, educational media developers, and policymakers in designing effective and sustainable strategies for implementing educational games in Senior High Schools (SMA/MA/SMK).